The Menhir as an Oral Tradition in Cattle-Raising Territories: First Geological Provenance Analyses at the Antequera Heritage Site, Spain - Cabello-Ligero, Lidia; Bueno-Ramírez, Primitiva; Armenteros-Lojo, Lidia; Suárez Padilla, José; Caro-Herrero, José Luis; De-Balbín-Behrmann, Rodrigo; Barroso-Bermejo, Rosa; Vázquez-Martínez, Alia; Durán-Velasco, Juan José; Durán-Laforet, Sergio; Jordá-Bordehore, Rafael; Morales-García, Raquel; et al. (MDPI, 2025)
The great megalithic sites reveal an extended use of their monuments. In Late Prehistory, in Protohistory, and even in historical times, dolmens remained visible references on the landscape and were central for navigating it. The megaliths of Menga, Viera, and Romeral provide quality data to confirm their continued relevance. Our aim here is to understand whether menhirs also played that role, using the area of Tierras de Antequera, which is connected to the sea, as a case study. With that goal in mind, a research project has been initiated through intensive archaeological field surveying, combined with the collection of testimonies from oral tradition and other archaeological tools such as GIS, geophysical prospection, photogrammetry and RTI, for the detection of engravings and paintings on some of the located landmarks. We present in this paper the first geological analyses in the megalithic territory of Antequera to determine the raw material of the menhirs that are studied and the geological outcrops from which they come.
Keywords: Monumentos megalíticos; Dólmenes - Antequera; Menhires; Megalithism; Menhirs; Dolmens; Geological provenance; Late prehistory; Oral tradition; Land survey